2014
DOI: 10.1186/1880-5981-66-45
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of the seasonal scale oscillations over Cachoeira Paulista (22.7°S, 45°W), Brazil

Abstract: The characteristics of long period atmospheric oscillations are studied using long-term meteor radar wind observations over a low-latitude Brazilian station, Cachoeira Paulista (22.7°S, 45°W). The semiannual oscillation (SAO) amplitude decreases gradually with altitude in the mesopause region, while the annual oscillation (AO) amplitude exhibits a minimum at mid-mesopause with significant interannual variability. The quasi-biennial oscillation (QBO) obtained by removing the SAO and AO from the zonal wind exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…1, since these long period oscillations have significant role in controlling the background wind. Observed asymmetry of the semiannual oscillation with higher amplitude during winter was also reported by past investigators from various low latitude locations over the globe (Hirota, 1978;Delisi and Dunkerton, 1988;Li et al, 2012;Guharay et al, 2014a). Delisi and Dunkerton (1988) concluded that higher planetary wave activity might have caused the large winter peak of the semiannual oscillation.…”
Section: Mlt Wind Variabilitymentioning
confidence: 58%
See 1 more Smart Citation
“…1, since these long period oscillations have significant role in controlling the background wind. Observed asymmetry of the semiannual oscillation with higher amplitude during winter was also reported by past investigators from various low latitude locations over the globe (Hirota, 1978;Delisi and Dunkerton, 1988;Li et al, 2012;Guharay et al, 2014a). Delisi and Dunkerton (1988) concluded that higher planetary wave activity might have caused the large winter peak of the semiannual oscillation.…”
Section: Mlt Wind Variabilitymentioning
confidence: 58%
“…Previous studies by Guharay et al (2014a) from the same station and Li et al (2012) from Maui (20.7°N, 156.4°W) found maximum amplitude of the annual and semiannual oscillations at 81 km considering the probing altitude range of 80-100 km and this is the reason for selecting this altitude bin in Fig. 1, since these long period oscillations have significant role in controlling the background wind.…”
Section: Mlt Wind Variabilitymentioning
confidence: 90%
“…If in addition to the increase in temperature the usual wintertime eastward zonal mean zonal wind at 10 hPa and at 60°N reverses its direction, then the event is called major or else minor (Andrews et al 1987). During SSW events, the interaction between enhanced planetary waves and tides and the interaction between tides and modified middle atmosphere modulate the tidal components, which register their signature in the upper atmospheric parameters (Jin et al 2012;Pedatella and Liu 2013;Guharay et al 2014). Also, nonlinear interaction between PWs and tides produces additional waves at the sum and the difference frequencies of the two original waves (Teitelbaum and Vial 1991) which fall mainly in the tidal domain.…”
Section: Introductionmentioning
confidence: 99%
“…The mean dynamical state of the equatorial middle atmosphere is significantly controlled by large-scale long period oscillations, i.e., semiannual oscillations (SAO) and quasibiennial oscillations (QBO) (Burrage et al 1996;Baldwin et al 2001;Guharay et al 2014a). These oscillations show downward propagation of their phases with altitude since they are driven by deposition of energy from upward propagating gravity waves, Rossby waves, Kelvin waves, etc.…”
Section: Introductionmentioning
confidence: 99%